Dispute Resolution in Business Sector: Comparing Indonesia and Singapore Arbitration Model - Kelvin Leong Chun Fai; Prasasti Dyah Nugraheni (Journal of Private and Commercial Law, 2023)
Dispute resolution within the business sector can be accomplished through either national arbitration institutions or international arbitration institutions. International arbitration serves as a process to settle civil disputes using a neutral third party, particularly in the context of business-related conflicts arising between parties engaged in international business agreements. Such arbitration is often specified through arbitration clauses included in these international business agreements, which are mutually agreed upon by the involved parties. One example of an international arbitration institution that specializes in resolving civil disputes, particularly those within the business sector, is the Singapore International Arbitration Center (SIAC) located in Singapore. The implementation of arbitration awards depends on the type of arbitration being conducted, whether it is a national arbitration award or an international arbitration award. During the preparation of this paper, the author utilized a normative-juridical research method, which involves relying on legal library sources and secondary legal materials to address existing legal issues. This paper aims to compare the legal foundations and the arbitration dispute resolution processes employed by the Indonesian National Arbitration Board (BANI) and the Singapore International Arbitration Center (SIAC). The research findings reveal that the legal basis for arbitration dispute resolution utilized by the Indonesian National Arbitration Board (BANI) differs from that employed by the Singapore International Arbitration Center (SIAC). Nevertheless, the processes and procedures for resolving arbitration disputes conducted by both institutions demonstrate notable similarities.